Selected Women Freedom Fighters of Karnataka during Gandhian Era - Asma K. Haliyal (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The history of freedom movement would be incomplete without saluting the contribution of women. The women in Karnataka played a unique & vital role in the freedom struggle during the Gandhian Era. Mahatma Gandhi led the freedom struggle from 1920 to 1947. His leadership attracted people from all walks of life. The women of Karnataka actively participating in movements like the Salt Satyagraha, No Tax Campaigns & Quit India Movement. The women of Karnataka state have contributed a lot in the freedom struggle. Some of the women participated of this era are Umabai Kundapur, Bellary Siddamma, T.Sunadamma, Kamaladevi Chattopadhya, Nagamma Patil, Krishnabai Panajikar Yashodara Dasappa Jayadevi Tai Ligade etc., Their courage resilience & unwavering commitment to freedom serve as a reminder of their sacrifices and shaping the Destiny of our beloved nation.